Modelling the habitat of a wild ungulate in a semi-arid Mediterranean environment in southwestern Europe: Small cliffs are key predictors of the presence of Iberian wild goat. (June 2016) - Lucas, Pablo M.; Herrero, Juan; Fernández-Arberas, Olatz; Prada, Carlos; García-Serrano, Alicia; Saiz, Hugo; Alados, Concepción L.
Abstract: After a drastic contraction in the species' range, the Iberian wild goat Capra pyrenaica (Schinz, 1838) has recolonized semi-arid steppe areas where the availability of resources is lower than it is in the species typical habitat. There is a gap in the habitat characteristics that allow the species to survive in an environment that lacks high cliffs and rocky outcrops. We hypothesize that microhabitat characteristics allow the species to find the resources necessary for survival in atypical areas. To test that, we measured several topographic variables (slope, distance to small cliffs and elevation) as well as land use/cover variables (distance to bushes, forests, agriculture, artificial and rivers). To model the habitat in the Middle Ebro Valley, Spain, we used data from 7-yr of monitoring of the species in an averaged-model with Generalized Linear Mixed Model (GLMM-Logit). Distance to small cliffs and distance to bushes explained most of the variance in the model which reflected a fragmented potential habitat. The fragmented structure of the habitat which might act as a metapopulation system, and the spatial configuration of fragments along rivers might act as corridors that favour the dispersal should be taken in consideration in the conservation and management of the species. Highlights: We model the habitat of Iberian wild goat Capra pyrenaica in a semi-arid area. Habitat is predominantly explained by small cliffs and bushes. High resolution DEM detects microhabitat. Small cliffs can act as buffer areas.